Antibody Complementarity-Determining Regions (CDRs) Can Display Differential Antimicrobial, Antiviral and Antitumor Activities - Polonelli, Luciano (Public Library of Science, 2008)
BACKGROUND: Complementarity-determining regions (CDRs) are immunoglobulin (Ig) hypervariable domains that determine specific antibody (Ab) binding. We have shown that synthetic CDR-related peptides and many decapeptides spanning the variable region of a recombinant yeast killer toxin-like antiidiotypic Ab are candidacidal in vitro. An alanine-substituted decapeptide from the variable region of this Ab displayed increased cytotoxicity in vitro and/or therapeutic effects in vivo against various bacteria, fungi, protozoa and viruses. The possibility that isolated CDRs, represented by short synthetic peptides, may display antimicrobial, antiviral and antitumor activities irrespective of Ab specificity for a given antigen is addressed here. METHODOLOGY/PRINCIPAL FINDINGS: CDR-based synthetic peptides of murine and human monoclonal Abs directed to: a) a protein epitope of Candida albicans cell wall stress mannoprotein; b) a synthetic peptide containing well-characterized B-cell and T-cell epitopes; c) a carbohydrate blood group A substance, showed differential inhibitory activities in vitro, ex vivo and/or in vivo against C. albicans, HIV-1 and B16F10-Nex2 melanoma cells, conceivably involving different mechanisms of action. Antitumor activities involved peptide-induced caspase-dependent apoptosis. Engineered peptides, obtained by alanine substitution of Ig CDR sequences, and used as surrogates of natural point mutations, showed further differential increased/unaltered/decreased antimicrobial, antiviral and/or antitumor activities. The inhibitory effects observed were largely independent of the specificity of the native Ab and involved chiefly germline encoded CDR1 and CDR2 of light and heavy chains. CONCLUSIONS/SIGNIFICANCE: The high frequency of bioactive peptides based on CDRs suggests that Ig molecules are sources of an unlimited number of sequences potentially active against infectious agents and tumor cells. The easy production and low cost of small sized synthetic peptides representing Ig CDRs and the possibility of peptide engineering and chemical optimization associated to new delivery mechanisms are expected to give rise to a new generation of therapeutic agents.